Agenesis of the lung associated with a chromosome abnormality (46, XX, 2p+). Issue 6 (December 1980) - Say, B; Carpenter, N J; Giacoia, G; Jegathesan, S
Abstract : We describe a patient with agenesis of the left lung who also had a chromosome abnormality, probably representing a duplication of the distal part of the upper arm of chromosome 2. In addition to this finding, the existence of familial cases of lung agenesis indicate that further studies are required for better understanding of the genetic aspects of this condition.